UMAT ISLAM DALAM MEMAKNAI ISU KRISTENISASI DI SALATIGA (Suatu Analisis Persepsi Berdasarkan Perspektif Teori Coordinated Management of Meaning) - Stefanie Theresia Permata; Royke Siahainenia; Sampoerno - (Cakrawala Jurnal Penelitian Sosial, 2015)
The issues of Christianization in Salatiga become the other side from a city that presumed was peacefully plural place. Begin from Salatiga impression as a Christian city because of the alleged huge housing Christian worship, The Christian domination in Salatiga cause of the largest Christian university faith-based local that lifted up named Satya Wacana Christian University, Until a long cases related to land disputes in Salib Putih at year end 2007 involving two groups of full of ambition on behalf of Islam and Christian that making the issue continues to roll in speculation without clarification. This research aims to analyze how Salatiga’s moslem perception in defining the issues and factors that affect the perception. In order to refine the analysis in the fields of communication, this research also uses the concept of Coordinated Management of Meaning to understand the construction of the perception being created every informant. The results showed that the tendency of perception lies in the context of the majority and minority. The difference lies in the perception is factors among people (informant) , factors on the object of perception, and the factors on the situation. The factors that influencing informant itself is attitudes, interests, and experiences. Factors that influence the perception of an object is the movement, size, and proximity. While the perception of the factors influencing the situation is the time. Keywords : Issues of Christianization in Salatiga, Perception, Muslims – Christians, Majority – Minority.